Information sources for patients undergoing corneal refractive surgery: results from a cross-sectional patient survey from a single private center in Poland - Przewłócka, BSc, Katarzyna; Kanclerz, Piotr (Digital Journal of Ophthalmology, 2021)
Purpose To identify the information sources for patients undergoing laser vision correction. Methods Individuals who underwent corneal refractive surgery at a private practice from December 2017 to August 2018 and agreed to complete an anonymous questionnaire were included. The manifest refraction and surgical method was recorded and correlated with the questionnaire results. Results Data collected from 126 patients (mean age, 32.8 ± 8.6 years; 55.6% women) were analyzed. Of 121 patients, 120 (99.2%) identified the Internet as a source for information on refractive surgery, and 71 of 119 (59.7%) noted that the clinic’s website influenced their choice of clinic. Patients with high myopia more commonly used contact lenses and had considered undergoing refractive surgery for a longer time compared with patients with other refractive errors (P < 0.01 and P < 0.01, resp.). Patients with hyperopia were less likely to know their own refractive error (P = 0.02). Conclusions In this patient cohort, the Internet was the main source of information for those undergoing refractive surgery.